Review of Islamic Law Regarding the Application of the Blue Economy to the Use of Organic Waste as Alternative Feed Materials (Study of Freshwater Fish Farming Community): Kajian Hukum Islam tentang Penerapan Ekonomi Biru terhadap Pemanfaatan Sampah Organik sebagai Bahan Pakan Alternatif (Studi Komunitas Budidaya Ikan Air Tawar) - Handayani, Nining Setyowati; Apriantoro, Muhamad Subhi; Assyafi, Vanissa; Tanasya, Nasya; Adabi, Risma Tamma (Prosiding University Research Colloquium, 2023)
This study seeks to determine how the Blue Economy is implemented in using organic waste as an alternative feed ingredient and what Islamic law has to say about managing organic waste as an alternative feed ingredient. Using a deductive case study methodology, the qualitative research method employs a case study approach. The data sources consisted of primary data obtained from direct interviews with the cultivator's head and secondary data obtained from journal references. According to the findings of this study, the Blue economy can be implemented by utilizing organic waste as an alternative feed ingredient for catfish in the following ways: 1). Community outreach regarding activities, 2). The community separates its trash, and officers collect it from the residents' homes, 3). Waste will be provided for consumption by larvae, 4). In addition to pellet feed, Maggots will be fed to catfish as an alternative food source. This activity has the potential to reduce environmental pollution and produce no waste. Maggots can save money on pellet purchases and have promising prospects as an alternative feed that reduces waste accumulation. Using alternative fish feed ingredients with Maggot does not violate Islamic law and does not affect the halal status of the fish fed the alternative elements.